Isolation, Identification and Percentage Hyphae of Endophytic Fungi in Gemitir Plant (Tagetes erecta L.) at Some Areas in Bali - Rahayu, Bekti Revi; Proborini, Meitini Wahyuni; Darmayasa, Ida Bagus Gede (Metamorfosa: Journal of Biological Sciences, 2019)
Endophytic fungi are found in roots, stems, leaves, flowers, fruit, until rhizosphere in soil area, where the fungus is widely used as an antifungal, biostimulan, antibacterial, and many more. Gemitir is one plant which widely cultivated in some areas in Bali. In Bali this plants use as a material for upakara , ornamental plants and herbs. This study was conducted to determine the type and different kind of endophytic fungi and to see the percentage of endophytic fungal hyphae in the roots, stems, and leaves on gemitir which taken at different locations. Sampling was taken at the Pangsan-Badung, Angseri-Tabanan Regency and Temesi-Gianyar. The sampling method which used is the diagonal method with five sample points. Isolation and identification process was carried out in the Laboratory of Plant Taxonomy (Mycology), State University of Udayana in January-March 2017. In this study of 15 species successfully identified to the genus level that belongs to the six genera namely Alternaria, Aspergillus, Botrytis, Trichoderma, Penicillium and Syncepalastrum. Total of fungal colonies in most samples were found at research location A (Pangsan-Badung Village) and percentage of highest endophytic fungal hypha existed at location C (Temesi-Gianyar Village).